Heterojunction ZnO on silicon for potential UV to visible photodetector utilising SILVACO TCAD effect of thickness and doping / A. Azmi Ahmad ... [et al.] - Azmi, Azila; Abd Rahim, Alhan Farhanah; Mohd Razali, Nor Shafika; Radzali, Rosfariza; Mahmood, Ainorkhilah; Hamzah, Irni Hamiza; Abdullah, Mohd Hanapiah; Mohamed, Mohamed Fauzi Packeer (Universiti Teknologi MARA, Pulau Pinang, 2022)
In this work, the study of heterojunction Zinc Oxide on Silicon to enhance UV photodetector performance has been conducted. The study was carried out using a SILVACO ATLAS device simulator. There are two parameters studied in this project are: to find the best thickness of ZnO and suitable doping concentration of ZnO on the silicon substrate as a photodetector device. There are three different thicknesses of ZnO (0.5 μm ,1 μm and 2 μm) and four different doping concentrations of ZnO applied (1x1015 cm-3, 1x1019 cm-3, 1x1020 cm-3 and 1x1021 cm-3). The performance of the ZnO on Si as a photodetector was evaluated by dark and photo current-voltage (I-V) characteristics. It was found that the optimum thickness of ZnO is at 1 μm and the suitable doping concentration of ZnO is at 1x1021 cm-3 since with these values, the photocurrent response is high, and in spectral response, the peak value for both is depicted in a visible region, which is suitable as UV photodetector device criteria.